The Companion to Raymond Aron
XII, 304 p.
Keywords: This edited collection brings to light the rare virtues and uncommon merits of Raymond Aron, the main figure of French twentieth-century liberalism. The Companion to Raymond Aron is an essential supplement to Aron's autobiography Mémoires (1984) and main works, exploring the substance of his political, sociological, and philosophical thought.